The Jews and their civilization role under the role of the Mughals (603-923هـ/ 1207-1517). - Yousef, Tawfiq; Ahmed, Khattab (Humanities Journal of University of Zakho, 2022)
The Mughals controlled A wide geographic area as they met with different civilization, so the tried to build a bridge to communicate with the people of these civilizations, they benefited the cultural output of these nations in the different ways like agriculture , industry and medicine , where the the translated several medical book in to different languages, from Arabic to persian and vise versa , and from these languages the jews translated into Greek language. Drugs were found that reference back to Islam, Christianity and Judaism in the area occupied by Mughals. The study focused on two main axes about the cultural role of Jews in Applied sciences like medicine Mathmatic as well as humanities like philosophy , represented by poetry and prose, bellows comes a detailed study that.